Early Clinical Effects of Novel Partial D3/D2 Agonist Cariprazine in Schizophrenia Patients With Predominantly Negative Symptoms (Open-Label, Non-controlled Study) - Ivanov, Stanislav V.; Smulevich, Anatoly B.; Voronova, Evgeniya I.; Yakhin, Kausar K.; Beybalaeva, Tangyul Z.; Katok, Alena A. (Frontiers in Psychiatry, 2022)
Background: Because of Llimited efficacy of antipsychotics against negative symptoms in schizophrenia and new drugs with wider spectrums of clinical efficacy are very desirable. The newer 3rd generation antipsychotic cariprazine presents the unique mode of action acting as partial agonist predominantly for dopamine D3- and in lesser extent D2-receptors. Cariprazine is found to be effective in the treatment of negative symptoms in schizophrenia comparing to second generation antipsychotic risperidone. Objectives: To evaluate initial effects of cariprazine in schizophrenia patients with predominantly negative symptoms. Design and patients: Open-label, non-controlled study included 60 adult schizophrenia patients (F20 on ICD-10, 49% males) with predominantly negative symptoms (Positive and Negative Syndrome Scale, S factor score for negative and positive symptoms, PANSS-FSNS ≥ 15 and PANSS-FSPS < 19) treated with cariprazine (starting daily dose 1,5 mg followed by upward titration by 1,5 mg weekly up to 6 mg if needed) were assessed with PANSS, CAINS (The Clinical Assessment Interview for Negative Symptoms), CDSS (Calgary Depression Scale for Schizophrenia), and SAS (Simpson-Angus Scale for Extrapyramidal Symptoms) scales at baseline and on week 1, 2, and 4. Results: Most patients (75%) improved during 28 days of cariprazine treatment. At the end of assessment (day 28) mean starting total scores for negative symptoms on PANSS-NS and CAINS scales significantly (p<0.05) reduced by 4,3 and 4,9 respectively with no significant changes in depression symptoms (CDSS). Cariprazine tolerability was very good, only 4 patients discontinued because of TEAEs (akathisia, insomnia). Conclusions: The results of this study suggest early effect of cariprazine on negative symptoms at least in some schizophrenia patients with predominantly negative symptoms starting from 1-2 weeks of treatment and could be useful for determination of early clinical predictors for efficacy. Considering limitations of open-label design with no control groups these data need to be confirmed.